2017
DOI: 10.4103/0971-5851.203509
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma in situ of the cervix with superficial intraepithelial extension to the endometrium of lower uterine segment: A rare presentation

Abstract: Carcinoma of the cervix is the most common malignancy in women in India. Squamous cell carcinoma accounts for more than 70% of the cervical malignancies. Carcinoma of the cervix generally invades the uterine wall by direct extension with or without parametrial involvement, however, rarely can spread superficially to the inner surface of the uterus replacing the endometrium. It is an uncommon phenomenon for an in situ lesion of the cervix to have contiguous superficial spread to the endometrium. We report a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Another 4 (15.38%) had cervical stenosis (one case had stenosis post conization performed 16 years ago). [ 11 12 13 14 9 10 ] The cervix was firm flushed with vagina in 3 (11.54%) cases,[ 13 15 16 ] and a visible cervical mass was reported in 11 (42.31%) women. [ 4 12 13 17 18 19 20 21 ]…”
Section: Review and Discussionmentioning
confidence: 99%
“…Another 4 (15.38%) had cervical stenosis (one case had stenosis post conization performed 16 years ago). [ 11 12 13 14 9 10 ] The cervix was firm flushed with vagina in 3 (11.54%) cases,[ 13 15 16 ] and a visible cervical mass was reported in 11 (42.31%) women. [ 4 12 13 17 18 19 20 21 ]…”
Section: Review and Discussionmentioning
confidence: 99%
“…Because of the rarity of this phenomenon and limited data, prognostic significance and management guidelines Pathology International are lacking. [1][2][3] Even though our patient was closely followed up with cyto-colposcopic studies at regular intervals, she developed a sudden recurrence at an advanced stage 16 years following conization. In our patient, failure to detect recurrence at an early stage can be explained by the inadequate cyto-colposcopic study due to cervical stenosis.…”
Section: Le Tt Er To T He Edi T Ormentioning
confidence: 93%
“…Although previous studies have suggested that radiation plays a role in pathogenesis, a correlation has not been substantiated in other cases. [1][2][3] Moreover, Kushima et al reported five patients with a similar unusual superficial spread of cervical squamous cell carcinoma; on genetic evaluation, they demonstrated a single clonal process for these tumors with a frequent loss of heterozygosity of 6p, 6q, 11p, and 11q, loci known to be commonly lost in typical cervical squamous cell carcinoma. 5 Furthermore, such tumors (including the present case) exhibited positivity for p16, a surrogate marker for human papilloma viruses, in immunohistochemical analysis.…”
Section: Le Tt Er To T He Edi T Ormentioning
confidence: 99%
See 2 more Smart Citations